IMPACT OF HEALTH EDUCATION ON THE COMPLIANCE LEVEL OF LUNG TUBERCULOSIS PATIENTS TO PREVENT THE TRANSMISSION OF MYCOBACTERIA TUBERCULOSIS - Cheristina, Cheristina; Suaib, Maryam (Universitas Islam Negeri Alauddin Makassar, 2021)
Tuberculosis (TB) is caused by bacteria (Mycobacterium tuberculosis) which most commonly attacks the lungs. Eight countries account for two-thirds of new TB cases in the world, namely India, China, Indonesia, the Philippines, Pakistan, Nigeria, Bangladesh, and South Africa. So for that it is very necessary to take precautions so as not to infect family members by increasing knowledge through health education. This study aims to analyze the impact of health education on compliance with pulmonary tuberculosis patients in preventing transmission of Mycobacteria Tuberculosis. This study uses the design used in this study is a quasi-experimental design method with the method of one group pre and post-test design. The sample size of this research is 30 people. The health education method used is the individual method as a requirement for conducting research during the COVID 19 pandemic and the media used to provide health education is a poster. The tool used to measure compliance is a questionnaire. The results of the analysis showed that there was a significant effect on health education on the level of pulmonary tuberculosis patients to prevent transmission of mycobacterium tuberculosis (p value was 0.000). Advise nursing arrangements in implementing community and individual nursing care to implement nursing interventions, especially health education by paying attention to the methods and media used so that the health education information delivered can be accepted and implemented by patients.